High radiation resistant crystals for x-ray and γ-radiation detectors - Fochuk, Petro; Skliarchuk, Valerii; Bolotnikov, A.; James, Ralf; Zakharuk, Z (SPIE, 2021)
Electrophysical properties of Hg2MnInTe6 single crystals grown by the modified zone melting method were studied. To expand the band-gap, a multiple part of Hg in 3(HgTe)-In2Te3 was replaced by an isovalent metal with a smaller ionic radius - Mn. Single crystals had n-type conductivity and possessed a resistivity of ρ≈5×106 cm (293 K), which was determined from the linear region of the current-voltage (I-V) characteristics for In/Hg2MnInTe6/In structure with two ohmic contacts. The product µτ≈ (1.7-3.4)×10-4 V-1 cm2 is determined. Compensation degree (≈ 0.99) of the semiconductor material and the energy position of deep level Ed ≈ 0.37-0.4 eV responsible for the dark conductivity were determined from measurements of the temperature dependence of the resistivity and space-charge limited currents (SCLC). From the optical measurements, the band-gap of single crystals was determined, which is equal to Eg = 1.15 eV (293 K). Au/Hg2MnInTe6/In structures with rectifying contacts were fabricated.
Keywords: radiation-resistant single crystals; Hg2MnInTe6; compensation degree; ohmic contact; Schottky contact; SCLC